Web Based Fixed Asset Management Information System Using the Waterfall Method (Case Study: National University): Web Based Fixed Asset Management Information System Using the Waterfall Method (Case Study: National University) - Listrina Turnip; Agung Triayudi; Ira Diana Solihati (Jurnal Mantik, 2020)
Asset Management is one of important keys in institutions. Therefore, each asset that is owned must be optimally, effectively and efficiently managed in order to give proper advantages to Institutions. The National University is the oldest private University in Jakarta. The National university has a lot of assets to support its operational such as computers, air conditioning, vehicles, laboratory equipment and etcetera. Currently the asset management systems at National University is still using Microsoft excel. it causes the process of the asset Recording, asset maintenance and asset Report at national university are less Optimal. it takes longer time to trace the data of the assets. To overcome the issue, an Information system is needed. This Research Uses waterfall method. This information system (of fixed asset management) is created using PHP programming language and using MYSQL as the database. The presence of this website-based (fixed assets management) information systems hopefully can facilitate the general administration officer to work more effective and efficient in managing the assets.